Detection of new-onset atrial fibrillation in heart failure patients using daily non-invasive ECG monitoring in the TIM-HF2 telemedicine trial. (25th November 2020) - Stegmann, T; Koehler, K; Schulze, M; Laufs, U; Wachter, R; Koehler, F
Abstract: Background: Heart failure (HF) and atrial fibrillation (AF) impair the prognosis when they occur concomitantly. Recent telemedical studies suggest that HF patients with AF may derive a greater benefit from telemedicine care but the results are inconsistent. The rate of newly detected AF in HF patients by daily non-invasive electrocardiogram (ECG) monitoring is unknown and a possible influence on the outcome of remote patient management (RPM) remains unclear. Purpose: We aimed to investigate the detection of new atrial fibrillation in patients assigned to RPM in comparison to patients assigned to usual care (UC) in the TIM-HF2 trial. Methods: The prospective, multicentre and controlled TIM-HF2 trial randomised 1538 patients (765 RPM, 773 UC). All patients had a 12-channel ECG at baseline and after one year at the final study visit. Patients who were assigned to RPM additionally transmitted a daily ECG to the telemedical centre (TMC). We excluded all patients with pacemaker including implantable cardioverter defibrillator (ICD) or cardiac resynchronisation therapy (CRT) in the baseline ECG, leaving 879 patients for analysis (RPM: 442 and UC: 437). The patients were stratified into patients with SR and patients with AF according to the rhythm documented at baseline. The primary endpoint of this analysis was newly documented AF within one year after randomisation. We analysed the daily to the telemedical centre transmitted ECGs of patients assigned to RPM with the documented rhythm status of the ECGs performed at the final study visit of patients assigned to UC. Results: 569 patients had SR and 310 patients had AF at baseline. The proportion of patients with AF was nearly the same in the RPM (159, 36.0%) and the UC (151, 34.6%) group. 68 patients (24.0%) were detected with new atrial fibrillation in the RPM group compared to 22 patients (7.8%) in the UC trial arm during the one-year follow-up (p<0.001, number needed to screen 6). Conclusion: In patients with heart failure and daily ECG transmission, atrial fibrillation was detected three times more frequently in comparison to usual care within one year. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The TIM-HF2 study was supported by a research grant of the German Federal Ministry of Education and Research (grant numbers 13KQ0904A, 13KQ0904B, 13KQ1104A). The TIM-HF2 study was a part of the research and development project "Gesundheitsregion der Zukunft Nordbrandenburg – Fontane" (Fontane). The Fontane system was developed in private–public partnership (PPP) supported by research and development grants from the German Federal Ministry of Education and Research, the European Regional Development, and the Federal State Brandenburg.